Resposta :
Resposta:
25+(15+6:3)x5-10=
25+(15+2)x5-10=
25+17x5-10=
25+85-10=
110-10=
100
explicação passo-a-passo:
![Ver imagem RAFER1527](https://pt-static.z-dn.net/files/d47/6ed48f8a16c247b609c2b6aa4266c526.jpg)
Resposta:100
Explicação passo-a-passo:
25+(15+6:3)×5-10=
25+(15+2)×5-10=
25+17×5-10=
25+85-10=
=100
Resposta:
25+(15+6:3)x5-10=
25+(15+2)x5-10=
25+17x5-10=
25+85-10=
110-10=
100
explicação passo-a-passo:
Resposta:100
Explicação passo-a-passo:
25+(15+6:3)×5-10=
25+(15+2)×5-10=
25+17×5-10=
25+85-10=
=100